Enhancing Students’ Reading Comprehension through Think-Pair-Share Technique in EFL Classroom - Intan Susana; Lutin Nur Rohmi R.; Lilik Mahmudah (Universitas Islam Balitar, 2026)
Reading comprehension is a fundamental component of English as a Foreign Language (EFL) learning at the senior high school level. However, many students experience difficulties in understanding texts due to limited vocabulary mastery, low reading motivation, and passive learning environments. This study aims to enhance students’ reading comprehension through the implementation of the Think-Pair-Share (TPS) technique. This research employed Classroom Action Research (CAR) design consisting of two cycles following the Kemmis and McTaggart model. The participants were 28 eleventh-grade students of a classroom in senior high school inSMA mambaus sholihin 2 Blitar. Data were collected through reading comprehension tests, classroom observation sheets, and field notes. The quantitative data were analyzed descriptively using mean scores and mastery percentages, while qualitative data were analyzed to support the interpretation of findings. The results shown a significant improvement in students’ reading comprehension and classroom participation. The mean score increased from 62.4 in the preliminary study to 67.8 in Cycle I and 81.8 in Cycle II. Furthermore, students demonstrated higher engagement, confidence, and collaboration during reading activities. The findings indicate that Think-Pair-Share is an effective cooperative learning technique for improving reading comprehension in EFL a classroom at the senior high school level in SMA Mambaus Sholihin 2 Blitar.